EFEKTIVITAS KEBIJAKAN MONETER INKONVENSIONAL TERHADAP STABILITAS MAKROEKONOMI KELOMPOK ADVANCED ECONOMIES SERTA KELOMPOK EMERGING MARKET & DEVELOPING ECONOMIES: STUDI KASUS PANDEMI COVID-19 - Ananda Marco Ramadhan Sialagan; Tiara Nirmala; Dian Fajarini (Yayasan Education and Social Center, 2026)
The COVID-19 pandemic triggered the largest economic crisis since The Great Depression of 1929–1933 and prompted central banks worldwide to massively adopt Unconventional Monetary Policy (UMP). This study comparatively analyzes the effectiveness of UMP during the COVID-19 pandemic across 10 Advanced Economies (AE) and 10 Emerging Market & Developing Economies (EMDE) spanning the sub-regions of Eastern Europe, Southeast Asia, and Latin America. Utilizing a qualitative multiple case study approach with source triangulation, this research finds that UMP in AE was highly effective in stabilizing financial markets through the portfolio balance channel; but the transmission to the real sector remained partial due to persistent Zero Lower Bound (ZLB) conditions and liquidity traps. Conversely, UMP in EMDE was more market-stabilizing rather than macro-stimulating, operating on a smaller scale (0.3–10% of GDP) but supported by the flexibility of the still-available interest rate channel. Three primary structural factors explain the difference in effectiveness between the groups: (1) the policy cycle position (ZLB vs. non-ZLB); (2) the depth of financial markets; and (3) the central bank credibility. These findings underscore that effectivity of UMP does not operate independently; rather, but is heavily determined by the broader policy ecosystem.